2015
DOI: 10.1080/02701367.2015.1042354
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Normative Reference Values for Handgrip Among Hungarian Youth

Abstract: Muscle strength as determined by handgrip has distinct age-related patterns in boys and girls. We have accounted for biological age differences and developed norm-referenced values that can be used to interpret handgrip assessment scores obtained from school-aged children in Hungary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 36 publications
6
28
0
1
Order By: Relevance
“…The results of our study suggest that high jump and long jump performances progress to a similar degree to jumping abilities measured with typical field tests like counter movement jumps and/or standing long jumps. In fact, the percentage improvements in high jump and long jump performances are similar to the improvements in the jumping abilities assessed with field tests in various populations from the ages of 13 to 16 [ 18 , 28 , 33 , 34 ] clearly suggesting the strong influence of growth and maturation in this age range. However, technical development and coaching high and long jump should take place in a structured manner during the growth and maturation development.…”
Section: Discussionsupporting
confidence: 62%
“…The results of our study suggest that high jump and long jump performances progress to a similar degree to jumping abilities measured with typical field tests like counter movement jumps and/or standing long jumps. In fact, the percentage improvements in high jump and long jump performances are similar to the improvements in the jumping abilities assessed with field tests in various populations from the ages of 13 to 16 [ 18 , 28 , 33 , 34 ] clearly suggesting the strong influence of growth and maturation in this age range. However, technical development and coaching high and long jump should take place in a structured manner during the growth and maturation development.…”
Section: Discussionsupporting
confidence: 62%
“…Fitness reference values in children and adolescents have been reported in many countries in Europe, the Americas, Oceania, and Asia. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, Tomkinson established European normative values for several physical fitness components in youth aged 9-17 years. 21 However, data on physical fitness levels in France are scarce, and only one study addressing the reference data for a French sample has been reported, and that study was restricted to adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Hand grip strength (HGS) is used as a means to predict health throughout an individual’s lifetime [ 1 , 2 ]. It is one of the field tests used the most to measure maximum isometric strength of the grip strength of both of the hands [ 3 ]. HGS is an important indicator that helps identify the level of development and degree of disability.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a growing number of research studies are appearing in the literature that propose using normative data to evaluate HGS during different stages of life and diverse regions of the world [ 3 , 8 12 ]. In general, standards are developed based on chronological age.…”
Section: Introductionmentioning
confidence: 99%